Highly efficient construction of angular polycycles - Yi Sun; Xiaobing Huang; Jun Ren; Zhongwen Wang (Nature Communications)
Abstract Angular tricyclic and polycyclic skeletons feature typical cores in an intriguing type of natural products. We herein report the Lewis acids-catalyzed dearomative (3 + 2) cycloadditions of donor-acceptor cyclopropanes with benzene ring, by which structurally complex and diverse angular tricyclic and polycyclic carbocycles were efficiently constructed from cheap and easily available feedstock and with convenient operation. This is also the example of (3 + 2) cycloaddition of a C3-synthon with the C = C of benzene. We believe this will demonstrate its potential in the total syntheses of natural products and drug discovery.